Perlindungan Terhadap Hak Anak Dalam Perceraian Menurut Hukum Keluarga Di Indonesia - Evi Marpiah; Eko Nursalim; Andi Muhammad Baso; Yudiansyah Yudiansyah; Fitriani Fitriani; Andryansyah Andryansyah (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2023)
The aim of this study is to clarify the legal certainty related to the protection of children who have been separated. The main issues that are central to this issue are: 1) What legal provisions apply to protect the well-being of children affected by the separation of parents? What rights are given to children? Studies using qualitative research methodology. Researchers, they do observational practice, conduct interviews with sources, and document relevant information. The aim of this study was to investigate the influence of religious courts in shaping laws relating to the protection of children affected by divorce. Can the decision of this religious court provide protection for the rights of the child? The current analysis has several implications: 1) Enhancing the role of judges in evaluating and determining custody forchildren victims of divorce. 2) It serves as a framework for judges to assess the rights of children to be recognized and fulfilled.